ANTI-CANCER ACTIVITY OF ASTER TATARICUS ON SCC-9 HUMAN ORAL SQUAMOUS CARCINOMA - Wang, Rui; Xiao, Sha; Niu, Zhongying (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Oral squamous carcinoma is a head and neck cancer, which is one of the types of malignant cancers. Present study evaluates the anticancer activity of Aster tataricus (AT) on SCC-9 human oral squamous carcinoma. Materials and Methods: Ethanol extract of AT was prepared by a standard procedure of maceration. AT extract was used in different concentrations like 10, 20, 40, 80, 160, 320 and 640 μg/ml for the evaluation of its anticancer activity. Effect of AT extract on SCC9 cells were observed by microscope and cytotoxicity by 3-(4, 5-Dimethylthiazol-2-Yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay. Moreover, clonogenic assay was used for the estimation of effect of AT extract on colony forming ability of SCC9 cells. Result: Result of the study suggested that treatment with AT extract causes cytotoxicity to SCC9 cancerous cells. In addition, AT extract treatment reduces clonogenic potential of SCC9 cell and it also inhibits the proliferation of cell significantly (p<0.001) in G2/M phase. Conclusion: Thus, given study concludes that AT extract effectively attenuates the growth of SCC-9 cancerous cells by the virtue of its cytotoxic and anti clonogenic activity.